An Unusual Case of Obscure Gastrointestinal Bleeding in a Patient with Coeliac Disease - M. Gwiggner; P. Patel (Case Reports in Gastrointestinal Medicine)
This paper describes the journey of a patient with coeliac disease who presented with overt obscure gastrointestinal bleeding. Upper and lower gastrointestinal endoscopy did not reveal a source of bleeding, but an abdominal CT scan detected abnormal lymphadenopathy and a wireless capsule endoscopy diagnosed a jejunal tumour, which was surgically removed. Gastrointestinal bleeding is rare in celiac disease. Malignant tumours of the small intestine are generally uncommon, but celiac disease represents a significant risk factor. Wireless capsule endoscopy has been a useful tool to investigate patients with obscure gastrointestinal bleeding.